TOXICITY TEST OF WATER-SOLUBLE FRACTIONS OF WASTE VEGETABLE OIL-BASED BIODIESEL AND BIODIESEL/DIESEL BLENDS ON Daphnia magna AND Allium cepa - Raisa
Biodiesel mishandling, such as biodiesel spills and leakage to water has potential risks of environmental pollution. This research was aimed to determine the toxicity of water-soluble fractions of waste vegetable oil-based biodiesel and biodiesel/diesel blends. Acute toxicity testing was conducted using Daphnia magna and Allium cepa for genotoxicity testing. The analyses of Total Petroleum Hydrocarbon (TPH) and Polycyclic Aromatic Hydrocarbon (PAH) was performed using Gas-Chromatograph Mass-Spectrophotometer (GCMS) method. Obtained LC 50 value for water-soluble fractions of 0% biodiesel (B0), B2, B5, B10, B20, B50, and B100 were 1.001 ppm; 1.279 ppm; 1.421 ppm; 1.577 ppm; 1.963 ppm; 3.026 ppm; and 3.157 ppm, respectively and chromosomal aberration percentage of B0, B5, B20, and B100 were 35,60%; 26,71%; 25,33%; and 9,0%, respectively at their EC 50. Results of correlation analysis between FAME either with LC 50 or percentage of chromosomal aberration showed a very strong correlation with Pearson correlation coefficients were 0,906 and -0,975, respectively. This research proved that there was a significant effect of F